2019
DOI: 10.1155/2019/2815890
|View full text |Cite
|
Sign up to set email alerts
|

Effect Analysis of Optical Masking Algorithm for GEO Space Debris Detection

Abstract: A method with high detection rate, low false-alarm rate, and low computational cost is presented for removing stars and noise and detecting space debris with signal-to-noise ratio (SNR>3) in consecutive raw frames. The top-hat transformation is implemented firstly to remove background, then a masking technique is proposed to remove stars, and finally, a weighted algorithm is used to detect the pieces of space debris. The simulation samples are images taken by 600 mm ground-based telescope. And a series of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Finally, the proposed method is compared with the MHT method for streak-like dim and small object detection [51] with SN R = 6, 3, 2, and 1.5. We also compared this method with the EAOM algorithm with SN R = 6, 3, [25]. The result is shown in Table 5, and it is observed that the proposed method has a better detection performance than that of the MHT and EAOM methods.…”
Section: Detection Performance Of Space Debris In Optical Image Sequencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the proposed method is compared with the MHT method for streak-like dim and small object detection [51] with SN R = 6, 3, 2, and 1.5. We also compared this method with the EAOM algorithm with SN R = 6, 3, [25]. The result is shown in Table 5, and it is observed that the proposed method has a better detection performance than that of the MHT and EAOM methods.…”
Section: Detection Performance Of Space Debris In Optical Image Sequencesmentioning
confidence: 99%
“…Yang et al [24] proposed an integration algorithm for the detection of weak space debris using incoherent scatter radar. Kong et al [25] proposed an optical masking algorithm for GEO space debris detection. Its detection probability reaches 94% and false-alarm rate is below 2% when the SNR is higher than 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many space debris detection methods have been designed in recent years. Kong et al 1 used top-hat and a masking method to remove most of stars in the scene, which was realized by using a ground-based telescope. Xi et al 2 used feature learning of candidate regions by a trained deep learning network to detect space debris, and one dimensional mean iteration method was proposed to correct the nonuniform background information.…”
Section: Introductionmentioning
confidence: 99%
“…GSO debris extraction algorithms can be divided into feature extraction based on shape difference and target enhancement through multi-frame cumulative energy. The main methods are masking method [23], continuous frame image comparison method [24], point spread function fitting method [25], mathematical morphology method [26] and so on. Generally, feature extraction algorithms have high complexity and require prior feature information of target or background; multi-frame energy accumulation algorithm needs to ensure efficient suppression of stars and background.…”
Section: Introductionmentioning
confidence: 99%